Collaborative Teacher Development on Teaching World Englishes - KAŞLIOĞLU, ÖZLEM (IGI GLOBAL, 2017)
Teachers play a central role in shaping education. Educational innovations succeed or fail with the teachers who shape it (Lieberman & Pointer Mace, 2008); thus teachers' professional development process should be given utmost importance and organized in a way that supports and promotes their growth. Traditional INSET programs based on knowledge-transmission are found to be ineffective in reaching this aim. The present case-study introduces a collaborative INSET program, in which the participating pre- and in-service teachers tried to develop their understanding of World Englishes and integrate it into teaching under the guidance of university supervisors. Data collected by means of interviews revealed that this process enriched the knowledge of the participants and enabled them to look at the relevant issue from a critical perspective.
Keywords: PROFESSIONAL-DEVELOPMENT